De Novo SCLC Transformation From KRAS G12C-Mutated Lung Adenocarcinoma With Excellent Response to Sotorasib: A Case Report - Takanori Ito, MD; Issei Oi, MD, PhD; Zentaro Saito, MD; Takuma Imakita, MD; Osamu Kanai, MD; Kohei Fujita, MD, PhD; Hiromasa Tachibana, MD; Koki Moriyoshi, MD, PhD; Tadashi Mio, MD, PhD (JTO Clinical and Research Reports, 2023)
The transformation to SCLC is a known mechanism of resistance against molecularly targeted therapies. This study reports a patient with untreated lung adenocarcinoma, characterized by a KRAS G12C mutation, which transformed into SCLC before treatment. Both the adenocarcinoma and SCLC components were responsive to sotorasib.